A virtual reality-based intervention for surgical patients: study protocol of a randomized controlled trial - Georgescu, Raluca Diana (Trials, 2021)
BACKGROUND: Pain after surgery is normal, and treatments, including both pharmacological and psychological components, are fundamental for proper postoperative care. While several trials have investigated the analgesic effect of traditional non-pharmacological treatments, such as cognitive behavior therapies, the newer ways of delivering psychological interventions for pain after surgery are scarcely investigated. The aim of this randomized controlled trial (RCT) is to determine if delivering the psychological content through virtual reality (VR) along with the standard pharmacological treatment return better pain relief outcomes than standard care in adult patients following surgery. METHODS: This is a protocol of a parallel RCT conducted in one community hospital. In order to test the efficacy of VR environments for reducing pain intensity, in the following day after surgery, adults (18 to 65 years) will be randomly assigned to either (1) standard treatment after surgery (control group) or (2) VR based intervention along with standard treatment. It is intended that a minimum of 30 patients be recruited in each group. For estimating the intensity of pain, both self-report and physiological measures will be used. Repeated measures of pain outcomes will be taken before and after the intervention. Moreover, for allowing an in-depth investigation of the effect of VR environments, the primary outcome will be complemented with measures of the adverse effects, level of immersion, and level of presence in the VR environment. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13063-021-05196-7.